THE EFFECT OF CRUDE PROTEIN HALIMEDA SP. ON CYPRINUS CARPIO INFECTED KOI HERPES VIRUS ON EXPRESSION OF MAJOR HISTOCOMPATIBILITY COMPLEX CLASS-1 - Yanuhar, Uun; Wahyuningtyas, Rika (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2017)
Halimeda sp. is a kind species of macroalgae that abundant grow in Indonesia. The utilization of Halimeda especially protein for disease prevention caused by the virus has not been done to the fish. The purpose of the study is to know the treatment of crude protein Halimeda sp on Cyprinus carpio infected by Koi Harvest Virus (KHV) on the expression of Major Histocompatibility Complex (MHC) class 1. MHC class-1 is one of the immune adaptive response on fish like this C. carpio. The methods are isolation of crude protein Halimeda sp, purification of crude protein, Haemagglutination (HA) test and dot blot test. The result shows that the crude protein of Halimeda sp. can produce of adaptive immune response like MHC class 1. MHC class-1 has the function of the immune system for maintenance of virus attacks directly. Responsible of treatment crude protein Halimeda sp. on C. carpio can be showed quantitatively using the dot blot test result. The conclusion is the crude protein of Halimeda sp. able to activate the MHC class I and to inhibit the proliferation of the KHV and maintenance of the fish cell of C. carpio..